Appraising the Quality of Systematic Reviews of Dysphagia Treatments post-Stroke - Charalampous, Chrysovalanto (Department of Rehabilitation Sciences, Faculty of Health Sciences, Cyprus University of Technology, 2021)
Background: There are many reviews in the field of post-stroke dysphagia, providing valuable findings about treatments and intervention for patients. However, their assessment in terms of their design and content could provide more insights about their overall quality for post-stroke dysphagia management. Aims: To appraise the quality of systematic reviews of randomized controlled trials (RCTs) regarding the treatments used for patients with post-stroke dysphagia using the AMSTAR 2(A Measurement Tool to Assess Systematic Reviews) instrument. Methods and Procedures: A systematic review of systematic reviews of randomized controlled trials was conducted following the PRISMA guidelines. the databases Cochrane Database of Systematic Reviews, PubMed, Medline were searched rigorously for systematic reviews concerning post-stroke dysphagia treatments that met the inclusion criteria. all features concerning the conduct of each systematic review was critically assessed through the AMSTAR instrument. Results: Six systematic reviews met the inclusion criteria, of which the majority found to be of low quality (4 studies), critically low (1 study) and high-quality (1 study), as the assessment through AMSTAR 2 indicated. Conclusions: The quality of conduct of included systematic reviews of RCTs regarding the post-stroke dysphagia treatments found to be low. The effectiveness of the dysphagia treatments is unclear due to several problems regarding intervention protocols and small number of participants. These findings indicate the need for the development of systematic reviews with higher methodological quality through which more generalized results could be obtained in relation to the most efficient treatments for post-stroke patients with dysphagia.
Keywords: Post-stroke dysphagia; Systematic reviews; Dysphagic patients; Dysphagia rehabilitation; Treatment